Systematic Literature Review on the Integration of Digitalization and Sustainability in Local Community-Based Strengthening Local Economic Development Strategies - Muhammad Distian Andi Hermawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This study examines the integration of financial technology (fintech) and green economy principles to promote sustainable gold trading in Indonesia, addressing the persistent challenges of environmental degradation, low transparency, and inefficiencies within the gold value chain. Unsustainable mining practices and limited traceability mechanisms have contributed to ecological damage and questionable supply-chain accountability. To respond to these issues, the research aims to analyze how fintech-based innovations such as blockchain, digital payments, and algorithmic monitoring can strengthen environmental governance, increase transparency, and improve trading efficiency in alignment with green economy goals. A quantitative research method was employed, involving the distribution of structured questionnaires to 250 respondents comprising investors, digital gold users, and fintech platform customers. Data were analyzed using structural equation modeling to assess the influence of fintech adoption, environmental awareness, and regulatory support on sustainable trading behavior. The results indicate that fintech adoption significantly enhances user trust, transaction transparency, and supply-chain accountability. Moreover, green economy awareness positively moderates users' preference for environmentally responsible trading platforms. Regulatory support further strengthens the ecosystem by providing a formal framework for environmental standards and digital verification processes. Overall, the study demonstrates that the synergy between fintech and green economy principles effectively drives sustainable gold trading practices in Indonesia. It highlights the need for stronger multi-stakeholder collaboration involving regulators, fintech companies, and environmental institutions to ensure responsible resource utilization while maintaining market competitiveness. The findings offer strategic insights for policymakers and industry actors seeking to accelerate sustainable digital transformation within the commodity sector.